Activation of meiotic recombination by nuclear import of the DNA break hotspot-determining complex in fission yeast - Wintrebert, Mélody (J Cell Sci, 2021)
Meiotic recombination forms crossovers important for proper chromosome segregation and offspring viability. This complex process involves many proteins acting at each of the multiple steps of recombination. Recombination initiates by formation of DNA double-strand breaks (DSBs), which in the several species examined occur with high frequency at special sites (DSB hotspots). In Schizosaccharomyces pombe, DSB hotspots are bound with high specificity and strongly activated by linear element (LinE) proteins Rec25, Rec27 and Mug20, which form colocalized nuclear foci with Rec10, essential for all DSB formation and recombination. Here, we test the hypothesis that the nuclear localization signal (NLS) of Rec10 is crucial for coordinated nuclear entry after forming a complex with other LinE proteins. In NLS mutants, all LinE proteins were abundant in the cytoplasm, not the nucleus; DSB formation and recombination were much reduced but not eliminated. Nuclear entry of limited amounts of Rec10, apparently small enough for passive nuclear entry, can account for residual recombination. LinE proteins are related to synaptonemal complex proteins of other species, suggesting that they also share an NLS, not yet identified, and undergo protein complex formation before nuclear entry. This article has an associated First Person interview with Mélody Wintrebert, joint first author of the paper.